Percepciones de los socios y no socios cooperativistas sobre la satisfacción laboral - Gargallo Castel, Ana; FREUNDLICH, Fred (REVESCO. Revista de Estudios Cooperativos, 2010)
Nowadays there is an increasing interest in the area of the firm’s management for the development of the social corporate responsibility (SCR) and the need to develop a suitable management of the human resources. Peculiarities of the cooperative companies provide a particular frame for the analysis of management of human resources, specially in case of the cooperatives of work, where work is the assets which is put jointly and where workers and members work together. It will generate specificities for the management of the human resources. In this study we analyze the perceptions of the determinants of job satisfaction of both groups. The information has been provided by a survey to 250 workers of a large cooperative. Our results reveal differences in the perceptions of members and non-members of the cooperative about the determinants of job satisfaction, which allows offering recommendations to favour job satisfaction.
Keywords: Satisfaction; Cooperatives; Human resources; Social responsibility